Highly efficient all-inorganic perovskite solar cells with suppressed non-radiative recombination by a Lewis base - Wang, Jing; Zhang, Jie; Zhou, Yingzhi; Liu, Hongbin; Xue, Qifan; Li, Xiaosong; Chueh, Chu-Chen; Yip, Hin-Lap; Zhu, Zonglong; Jen, Alex K. Y. (Nature communications, 2020)
All-inorganic perovskite solar cells (PVSCs) have drawn increasing attention because of their outstanding thermal stability. However, their performance is still inferior than the typical organic-inorganic counterparts, especially for the devices with p-i-n configuration. Herein, we successfully employ a Lewis base small molecule to passivate the inorganic perovskite film, and its derived PVSCs achieved a champion efficiency of 16.1% and a certificated efficiency of 15.6% with improved photostability, representing the most efficient inverted all-inorganic PVSCs to date. Our studies reveal that the nitrile (C-N) groups on the small molecule effectively reduce the trap density of the perovskite film and thus significantly suppresses the non-radiative recombination in the derived PVSC by passivating the Pb-exposed surface, resulting in an improved open-circuit voltage from 1.10 V to 1.16 V after passivation. This work provides an insight in the design of functional interlayers for improving efficiencies and stability of all-inorganic PVSCs. There has been a hot competition to optimize the device performance for all-inorganic perovskite solar cells. Here Wang et al. employ a Lewis base molecule to suppresses the non-radiative recombination in the inverted device and achieve a champion efficiency of 16.1%.